1996
DOI: 10.1097/00006123-199602000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medulloblastoma Resections on Outcome in Children: A Report from the Children's Cancer Group

Abstract: We reviewed the data of children with high-stage primitive neuroectodermal tumors (medulloblastomas) who were treated on Children's Cancer Group-921 protocol to evaluate the correlation between tumor resection and prognosis. Patients enrolled in the study had either tumors that were operatively categorized to be Chang tumor stage 3b or 4, postoperative residual tumors > 1.5 cm2, or evidence of tumor dissemination (Chang metastasis Stages [M Stages] 1-4) at diagnosis. Resections were analyzed in two ways, as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(147 citation statements)
references
References 15 publications
5
126
1
12
Order By: Relevance
“…Studies have shown that patients with less then 1.5 cm 2 residual disease had improved survival. [5][6][7] Some patients might require a ventricular shunt or third ventriculostomy prior to resection of the tumor. The majority of patients will have resolution of the hydrocephalus after tumor resection, but approximately 40% will require permanent shunt placement.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…Studies have shown that patients with less then 1.5 cm 2 residual disease had improved survival. [5][6][7] Some patients might require a ventricular shunt or third ventriculostomy prior to resection of the tumor. The majority of patients will have resolution of the hydrocephalus after tumor resection, but approximately 40% will require permanent shunt placement.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…However, the importance of a complete resection varies between the tumour types. A complete macroscopic resection is highly prognostic for ependymomas [1,2], whereas small amounts of residual medulloblastoma (up to 1.5cm 2 ) are not of prognostic significance if treated with radiotherapy and chemotherapy [3] and small residual masses of pilocytic astrocytoma may be observed without further treatment [4]. Histopathology is usually not available for several days after the operation and intraoperative histopathology is commonly used to inform the surgeons of the likely tumour type but the techniques available are not accurate [5] and this strategy does not allow patient-specific clinical management planning prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the predictive performance of current risk stratiWcation, which is entirely based on clinical variables, needs to be improved because of the dismal prognosis of children with tumor relapse, and because of relevant treatment-induced long-term eVects of survivors [21]. Clinical staging systems based on age, metastatic stage at diagnosis and, in some studies, extent of surgical resection have so far been the most useful methods for the stratiWcation of patients into standard and high risk therapy groups [1,26,27]. Additionally, after reWnement of the histological classiWcation of MB in the 2007 WHO classiWcation, the histological subtype is of potential prognostic relevance: large cell/anaplastic MB behaves more aggressively, while nodular/ desmoplastic variants show a more favorable clinical course as compared to the large group of classic MB [3,5,7,10,13,14,17].…”
Section: Introductionmentioning
confidence: 99%